Is It Polite to Hiss?: Nonverbal Sound Objects as Markers of (Im)politeness in Korean - Brown, Lucien; Kim, Hyunji; Winter, Bodo (Frontiers in Communication, 2022)
This paper explores the politeness-related functions of an ingressive hissing-like sound that occurs frequently in Korean and which is typically transcribed as ssup. This nonverbal sound is produced by drawing air alongside the tongue or between the teeth and may appear either before the production of a turn, or during turn production. Previous studies have shown that Korean speakers produce more frequent hisses when addressing status superiors. This suggests a politeness-related function, particularly given the importance of marking social distance towards elders and superiors in Korean culture. In the current paper, we explore the pragmatic functions of these hisses in three distinct datasets (oral discourse completion task, dyad recordings, drama interactions). Our analysis shows that hisses perform four types of social actions: displaying delicacy, activity shift, word search, and conveying skepticism. Hisses occur at interactional or relational trouble spots to delay the progression of talk, while allowing the speaker to initiate or maintain their turn. They co-occur with other verbal and multimodal markers of hesitation. We thus see the underlying core meaning of hisses as being related to difficulty, uncertainty and hesitation, and the conveyance of reluctance to perform the problematic talk. The increased frequency of hisses and multimodal hesitation in interactions with status superiors shows us that speakers are trying to show more care and effort when interacting in situations where social distance exists. These results contribute towards our understanding of politeness as a multimodal and holistic phenomenon that is expressed across multiple verbal and nonverbal dimensions.